Pengaruh Penggunaan Aplikasi Microsoft Teams Terhadap Penyebaran Informasi Pada Karyawan PT Schneider Batam - Jukasni, Yollanda; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2023)
Microsoft Teams is a new collaboration platform that has become popular in the modern work environment, providing a wide range of features for communication and collaboration in the form of instant messaging, voice and video calling, and file sharing. The development of technology and information is an unavoidable reform in entering the 4.0 era. Users not only experience challenges in using new media but also have to be able to adapt to the media. This study aims to determine whether Microsoft Teams affects the dissemination of information to employees of PT Schneider Electric Batam. The research method used is descriptive quantitative method. The sampling technique used is random sampling technique, the sample in this study is 100 employees. Research data obtained from the results of the questionnaire. Data analysis techniques used descriptive statistical tests, classical assumption tests, simple linear regression and hypothesis testing. The research results from the use of the Microsoft Teams application are said to have a positive and significant effect on the dissemination of information because the value for using the application is significant 0.000 <0.05 and the t-count value of 7.812 is greater than the t-table value of 1.984. Keywords : Microsoft Teams Application, Influencing, Dissemination of Information